SUKUK VERSUS BONDS: MATHEMATICALLY LITERATURE STUDY - Murniati, Wahyuning; Sumarti, Novriana; Puspita, Dila (Journal of the Indonesian Mathematical Society, 2024)
Based on IIFM Sukuk Report 2022, global sukuk issuance has shown a single digit increase of around 7.72%, the highest value of yearly sukuk issuances to date. This fact shows that sukuk is increasingly popular and will continue to grow in the future, encourages more research related to this subject. Sukuk, as one of the innovative investment instruments in Islamic finance, is often equated to conventional bonds. However, the existing literature primarily concentrates on its structures and mechanisms, largely overlooking the pricing aspects of both sukuk and bonds. Therefore, this study will discuss pricing in mathematical terms for the two investment instruments discussed. More particularly, this paper covers the Indonesian Sukuk system’s operation. Numerical simulations have been done, using the characteristics of several varieties of Indonesian Sukuk and a variety of defined inputs. These mathematics simulation used to comprehend the technical aspects of sukuk and understand the principles of Islamic finance. The results of this study indicate that while some studies claim that sukuk's structure resembles bonds and that the pricing is determined accordingly, the comparison of both instruments prices provided no results consistent with the claims. Further study is required to examine the sukuk pricing mechanism, particularly in determining the value of profit sharing on sukuk.